Activation and mechanochemical breaking of C–C bonds initiate wear of diamond (110) surfaces in contact with silica. (March 2016) - Peguiron, Anke; Moras, Gianpietro; Walter, Michael; Uetsuka, Hiroshi; Pastewka, Lars; Moseler, Michael
Abstract: Diamond surfaces wear when sliding against silica – a much softer material. Although this plays a major role in chemical mechanical planarization of diamond or machining of rocks, the underlying microscopic mechanisms are hardly understood. Here, the stability of diamond (110) surfaces in sliding contact with amorphous silica and with amorphous silicon (a mechanically similar reference system) is studied by quantum-chemical simulations. Interfacial C–Si bonds with amorphous silicon are too weak to harm diamond (110) surfaces. Conversely, strong C–O and C–Si bonds form between silica and diamond. However, this alone is insufficient to challenge interfacial diamond-like C–C bonds during sliding. Analysis of local forces and electronic structure shows that bonding to silica can chemically activate C–C bonds between terminating carbon zigzag chains and bulk diamond when the zigzag chains stay aromatic. Mechanochemical breaking of these weak bonds and subsequent lifting of C–C–C zigzag units mark the onset of wear on diamond (110) surfaces. This is in contrast to the silicon case, where the higher interfacial bond density renders the diamond surface non-aromatic and diamond-like.